PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 - Nurul Izzah; Fajar Syaiful Akbar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The company's internal factors have an influence on the stock price. Besides that, the stock price is also influenced by the company's external factors. As a result, the purpose of this research is to determine the impact of internal and external factors on stock prices in LQ45 companies from 2017 to 2019. The sample was taken using the purposive sampling method. A total of 75 samples were taken from 25 companies during 3 observation periods. The analytical method used is multiple linear regression analysis. The independent variables in this research are asset growth, profit growth, dividend payout ratio, BI rate, and economic growth, and the dependent variable is LQ45 stock price. The findings revealed that LQ45 stock prices were affected by asset growth, profit growth, dividend payout ratio, BI rate, and economic growth all at the same time. Profit growth and dividend payout ratio have a significant effect on LQ45 stock prices, while asset growth, BI rate, and economic growth also have no effect on LQ45 stock prices.